From Online to Offline: Presentations of Self and Partner Searching Techniques among Women in Turkey on Dating Sites - Erdogan, Baris (European Scientific Journal, ESJ, 2022)
Online dating platforms (apps or websites) have become instruments that are increasingly used by women in their practices of looking for a partner for romantic and/or sexual purposes. This paper focuses on discussing women’s self-presentation (also called impression management) methods and their strategies for evaluating themselves as presented both offline and online within the context of habitus. To this end, field data were collected with the netnographic method on the dating site called “OkCupid”. Afterwards, 11 university-educated white-collar women who were users of this platform in Turkey were enrolled in a semi-structured in-depth interview. While dating sites have offered women new opportunities in the intimacy market within modern society, relationships that start online and continue offline may not provide the anticipated satisfaction among daters due to several structural and technical reasons. The results of our analysis indicate that firstly, this online platform creates the insatiable idea in the minds of daters that they will find a better partner candidate at any moment. Furthermore, it decreases the possibility that daters that like each other will make long-term investments in each other. Secondly, after the rationally-built presentation of the self on the online stage, the mystery which brought about the emotional attraction has been significantly removed from the offline stage.